Validity and reliability of the scale of attitudes towards the recycling and responsible use of paper in students of the UNMSM - Vargas Vargas, Gaby (2017)
The method of the study was psychometric because it was applied a set of procedures that allowed quantitative evaluation of psychological characteristics such as the validity and reliability of the scale of attitudes toward recycling and responsible use of paper. Likewise, the research aimed to elaborate the scale of attitudes towards responsible use of paper in students of the UNMSM. Done that I locate the study as technological research, whose product was the obtaining of the mentioned questionnaire; The method used for this purpose was the descriptive Correlational, with cross-sectional design, because the data were obtained in a single moment (Hernandez & Others 2001). The population consisted of 241 students. The sample design was probabilistic whose size was calculated with the Cochrane procedure at 0.05 of error and at a confidence level of 0.95, requiring a sample of 241 students to cover the mentioned requirements. Also the design of the research was of non-experimental type of transactional cut, because the data were obtained in a single moment. We can also mention that the study was applied type because it allowed to confront theories raised with reality. In addition the technique used was the test and the instrument of data collection the scale of attitudes toward recycling and responsible use of paper. The technique used corresponds to the fundamentals of psychometry to elaborate questionnaires that in the study was to measure attitudes towards recycling and responsible use of paper theoretically used the theory of Fishbein & Ajzen (1975), as conceptual guides. To prove the validity, the construct method was used using the internal consistency of the factors and total test. For reliability, we used the internal consistency test item total test and the method of the halves, in the first case using the Crombach formula and in the second with the Spearman formula. The normalization criteria were percentile scores and scalar T.